THE INFLUENCE OF LEADERSHIP STYLE ON WORK MOTIVATION OF EMPLOYEES AT THE OFFICE OF COMMUNITY AND VILLAGE EMPOWERMENT IN POLEWALI MANDAR REGENCY - Muh. Muhtadi Muchtar; Amiruddin Tawe, Tenri S.P Dipoatmodjo, Muhammad Ichwan Musa, Uhud Darmawan Natsir (CV. Adiba Aisha Amira, 2025)
This research aims to determine the influence of leadership style on the work motivation of employees at the Community and Village Empowerment Office of Polewali Mandar Regency. The variables in this research consist of the independent variable, namely leadership style, and the dependent variable, namely work motivation. The research method uses a quantitative approach with data collection techniques in the form of observations, interviews and questionnaires which were distributed to 47 respondents. The data analysis technique used is simple linear regression analysis with SPSS version 26 software to prove the hypothesis. The results of this research indicate that the application of a democratic leadership style has a significant effect on employee work motivation. Employees who feel involved in the decision-making process, receive clear communication, and feel attention to their needs tend to show higher levels of motivation in carrying out their duties and responsibilities.